3u-10=14

Simple and best practice solution for 3u-10=14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3u-10=14 equation:


Simplifying
3u + -10 = 14

Reorder the terms:
-10 + 3u = 14

Solving
-10 + 3u = 14

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + 3u = 14 + 10

Combine like terms: -10 + 10 = 0
0 + 3u = 14 + 10
3u = 14 + 10

Combine like terms: 14 + 10 = 24
3u = 24

Divide each side by '3'.
u = 8

Simplifying
u = 8

See similar equations:

| 4+(x-5)=2(3-x) | | 4x^2-28x+c= | | Z+20=6 | | (Xy^2)(x^2+3xy+9)=0 | | 2x^8+6x^8= | | 2(x+6)x^2=90 | | 21x^2y+2xy-8=0 | | 3(x-2)=5(2+3) | | h+h+4=218 | | y=x^5+6x+8 | | 14(y-7)+12y=16-70 | | 6+2(7x+2)=3 | | 5y=4x+12 | | -3x+3=5x-5 | | (3a+4b)(3a-4b)= | | x*1+3*1,5+(x-3)*2=19,5 | | 3x+37=97 | | x^2-4x+2=-1 | | X=15000+0.36(8600+0.2X) | | h+h+20=300 | | 3-(x-4)=4-(2x+5) | | 15-(-23)= | | 0=-x^2-9x+7 | | 28u^2-27u-10=0 | | .06(z-300)+.05z=.70z-205 | | 25+30=35+20 | | 0=x^4-4x^3-24x^2+20x+7 | | 5z(x-6y)+7(x-6y)=0 | | 3w-6=20 | | y=abs(4-x) | | -x^2-9x+7=0 | | 3(2x-8)-3=3(X-4)+6 |

Equations solver categories